Sistem Informasi Profil Umkm Desa Tirtajaya Berbasis Web Menggunakan Bilingual Bahasa Indonesia Dan Bahasa Inggris - Lusiana, Garnis (mijournal.org, 2024)
The rapid development of information technology has facilitated information access and is utilized in various fields, including MSMEs. The MSMEs in Tirtajaya Village, Bajuin Subdistrict, Tanah Laut Regency, consist of 26 businesses offering local products such as spices, herbal medicine, cakes, sambal, and chips. However, limited promotion has made them less well-known. To address this issue, a bilingual web-based Information System for the Profile of MSMEs in Tirtajaya Village (in Indonesian and English) was developed using the CodeIgniter 4 (CI4) framework. This system aims to serve as a platform for promotion and sales, opening opportunities to compete in the business world. It is supported by ERD, UML designs, and Figma interfaces, and implemented using the MVC design pattern. System testing through black box methods and UAT showed satisfactory results, with 100% success in black box testing and an average UAT score of 4.74 out of 5, proving the system works as expected and meets user needs. It is hoped that this system can promote and develop the MSMEs in Tirtajaya Village, enhance the welfare of the village community by increasing business opportunities, and attract foreign attention.